Why Valuing Wetland Ecosystem Services within the Nile Basin is Important for Wise Use - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2011)
Wetlands are important areas for social, cultural and economic benefits for local communities living in and around them. The Nile Basin region is endowed with rich and diverse wetlands supporting the livelihoods of millions of people covering 3% of the total Nile Basin area. Unfortunately, national and regional scale policies aimed at wetlands management in the Nile Basin region have not been inclusive of structures/frameworks or approaches that would contribute to evaluation of wetland ecosystem services to guide wise use of the wetland resources. In several cases, the implementation of these policies have focused on the direct benefits that can be realised from wetland ecosystems (an anthropocentric approach), thereby undervaluing the benefits of the wetlands. It is within this context that this policy brief explores the policy gaps, with the aim of providing policy recommendations based on empirical information. The overall recommendation therefore being the need to consider economic valuation of wetlands for the total value based on costs of alternatives.